2009
DOI: 10.1111/j.1559-1816.2009.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

From Intentions to Behavior: Implementation Intention, Commitment, and Conscientiousness1

Abstract: Implementation intentions are said to transfer control over goal‐directed behavior to situational cues, thereby automating initiation of the behavior (Gollwitzer, 1999). Alternatively, implementation intentions may be effective because they create commitment to the intended behavior. In an empirical study, implementation intentions regarding a simple task (rating TV newscasts) varied in their specificity. In addition, explicit commitment to the task was manipulated, and chronic conscientiousness was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
228
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(256 citation statements)
references
References 36 publications
9
228
2
2
Order By: Relevance
“…In fact, the meta-analysis by Klein et al demonstrated that goal commitment has positive effects on subsequent behaviour. In some cases this commitment is linked with intentions, as indicated by Ajzen, Czasch, andFlood (2009, p. 1359) who stated that "favourable intentions may be accompanied by different degrees of commitment to the intended action, and a heightened sense TOWARD A UNIFIED MODEL 13 of commitment increases the likelihood that the behaviour will be carried out". Indeed, Gibbons et al (1998Gibbons et al ( , p. 1164 proposed that "a central tenet [of the decision to commit to a particular behaviour] is that because all behaviours involve premeditation or planning, [and] the only proximal antecedent of a particular action is the individual's intention to engage in that action".…”
Section: Phase 3: Strengthening Transfer Commitmentmentioning
confidence: 99%
“…In fact, the meta-analysis by Klein et al demonstrated that goal commitment has positive effects on subsequent behaviour. In some cases this commitment is linked with intentions, as indicated by Ajzen, Czasch, andFlood (2009, p. 1359) who stated that "favourable intentions may be accompanied by different degrees of commitment to the intended action, and a heightened sense TOWARD A UNIFIED MODEL 13 of commitment increases the likelihood that the behaviour will be carried out". Indeed, Gibbons et al (1998Gibbons et al ( , p. 1164 proposed that "a central tenet [of the decision to commit to a particular behaviour] is that because all behaviours involve premeditation or planning, [and] the only proximal antecedent of a particular action is the individual's intention to engage in that action".…”
Section: Phase 3: Strengthening Transfer Commitmentmentioning
confidence: 99%
“…Orbell, Hodgkins and Sheeran (1997) found that if guidelines about when and where to perform a certain action are provided, it becomes more likely that the intention will be enacted. More specifically, Ajzen, Czasch and Flood (2009) found that participants are five times more likely to return a survey when there is an implementation intention. The authors also found that an implementation intention creates a sense of commitment to perform a certain behaviour, even if the implementation intention is not very specific.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…Even though behavioral intention as a surrogate for customers' actualized usage behavior has recently been challenged [37], intention-behavior correlations as high as 0.90 [16] and 0.96 [31] have been reported, although in most cases, predictive accuracy is more modest [1]. In the current research we operationalize behavioral intention as the best available indicator of B2B customers' future use of digital services.…”
Section: Behavioral Intentionmentioning
confidence: 99%